Increased expression of vascular endothelial growth factor associated with accumulation of lipids in Bruch's membrane of LDL receptor knockout mice. Issue 12 (18th November 2005) - Rudolf, M; Winkler, B; Aherrahou, Z; Doehring, L C; Kaczmarek, P; Schmidt-Erfurth, U
Abstract : Aim: To investigate the pathogenesis of age related macular degeneration (ARM) with respect to lipid accumulation within Bruch's membrane (BrM) in a knockout model with low density lipoprotein (LDL) receptor deficiency. Methods: LDL receptor deficient mice and C57BL/6 controls were fed a standard diet or a high fat (HF) diet. Plasma total cholesterol (pTC) was determined. Eyes were examined by transmission electron microscopy. Immunohistochemical staining for VEGF was performed. Results: pTC were highest in LDL receptor deficient mice after HF diet and elevated after standard diet compared to controls with and without HF diet. While BrM of controls did not exhibit any visible changes, membrane bound translucent particles were seen in all BrM of knockout mice. The amount of these particles was substantially increased and membranes were thickened after HF diet. VEGF staining was positive in knockout mice only and was located in retinal pigment epithelial cells, the outer plexiform layer, and photoreceptor inner segments. Most intensive VEGF expression was documented after HF diet. Conclusion: LDL receptor deficient mice exhibit an accumulation of lipid particles in BrM which is further increased after fat intake. VEGF expression is found in the outer retinal layers of LDL receptor deficient mice and appears to correlate with the amount of lipid particles present in BrM.